PENGARUH MEDIA TIMBANGAN YANG BERORIENTASI MODEL POLYA DAN KEMANDIRIAN BELAJAR MAHASISWA TERHADAP PEMAHAMAN KONSEP MATEMATIS MAHASISWA TADRIS MATEMATIKA STAIN GPA - Hilliyani, Hilliyani (Al-Khawarizmi, 2018)
Learning media is seen as a communication tool that bridges between abstract ideas and the real world, learning media also makes the process of interaction independence, communication and material delivery between educators and students so that it can take place in an appropriate and efficient manner. The purpose of this study was to determine the effect of the scales media oriented on the model of politics and learning independence on understanding the mathematical concepts of STAIN GPA mathematics students. The method used in this study is a quasi-experimental method. The subject of this study was a fifth semester mathematics student consisting of 26 students. Sampling from this study is by using population samples. Data collection before and after treatment was obtained from the test scores on the ability to solve mathematical questions in linear program subjects, PLSV and PTSLV. The test given consists of 10 questions in the form of essays. In addition to using the test in this study also used a questionnaire to see the independence of student learning which consisted of 22 item statements. The results showed that it was 15.65 ≥ 2.05 so that Ho was rejected and Ha was accepted, or in other words the use of the Polya model oriented scales media and learning independence could have a positive and significant effect on understanding the mathematical concepts of STAIN GPA Mathematics Students.